Effect of Vrn-1, Ppd-1 genes and earliness per se on heading time in Argentinean bread wheat cultivars - Gomez, Dionisio Tomas (2014)
Predicting phenology, in particular heading time, is crucial to avoid and/or minimize risk of damage offrost, drought and high temperatures during grain filling. Although some of the major genes controllingdevelopment, associated with photoperiod and vernalization responses, were identified, the associationbetween the molecular characterization of those genes and photoperiod sensitivity, vernalizationresponses and earliness per se has been poorly studied. The present study was conducted to determinethe effects of photoperiod and vernalization genes (and their allelic combination characterized by molecularapproach) on heading time and its correlation with the phenological parameters determined by fieldexperiments in a wide range of Argentine bread wheat commercial cultivars. Additionally, the associationbetween photoperiod and vernalization responses with earliness per se was analyzed. Molecularcharacterization showed that most of the commercial Argentine wheat cultivars available in the marketcorrespond to spring growth habit with dominant insensitive photoperiod alleles (SI) followed by springhabit sensitive to photoperiod (SS), while winter insensitive (WI) habit represented a minority group. Allgenotypes included in the present study (even those classified as SI and WI) were photoperiod sensitivewhen that trait was quantified from a physiological analysis as the slope of the relationship betweenduration of a particular phase and mean photoperiod sensed during the period between emergence andheading. SI showed lower photoperiod sensitivity than SS and WI, without clear differences betweenboth later groups. In all cases, photoperiod sensitivity was the main attribute that determined the differencesin time to heading even when vernalization requirements were not completely fulfilled in the WI.The genotypes with different photoperiod and vernalization allele combinations showed a wide range ofduration of earliness per se. However, differences in earliness per se did not show any particular associationwith the groups classified by molecular markers for photoperiod and vernalization. The informationincluded in the present study can be used to build a gene-based model for predicting phenology. However,the variations in photoperiod and/or vernalization sensitivity within the same allelic combinationcould still determine mismatching in the prediction of the models based on Ppd-1 and Vrn-1 genes.